Vanuatu : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that Vanuatu's real GDP growth rebounded to 2.4 percent in 2003, and the recovery continued in 2004 with growth of an estimated 3 percent. The improvement was bolstered by a strong supply response to a recovery in export prices and the liberalization of trading in two key exports (cocoa and copra), the discovery of new markets for kava following the ban by several countries in 2002, and higher tourist arrivals with an expansion in airline capacity to Vanuatu. Progress has also been made in strengthening Vanuatu's financial sector.